La consommation de substances psycho-actives chez les femmes détenues au Québec - Brochu, Serge; Biron, Louise; Desjardins, Lyne (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1996)
Compared to male offenders, very few studies have been published on drug use by female offenders. This paper, base on the interviews of 94 female offenders incarcerated aim to enlighten this obscure situation. Results indicate that drug use by female inmates is very important and, in some way problematic. It is not to say that their drug use cause crimes, but their drug problem need to be addressed thoughtfully.